Sliding mode-based adaptive resilient control for Markovian jump cyber–physical systems in face of simultaneous actuator and sensor attacks. (August 2022) - Yang, Hongyan; Han, Honggui; Yin, Shen; Han, Huayun; Wang, Pu
Abstract: The rapid development of Cyber–physical systems (CPSs) poses nontrivial challenges to the issue of cyber-security. In this work, an improved sliding mode control strategy against time-varying state-dependent actuator and sensor false data injection (FDI) attacks is proposed to design an adaptive resilient control scheme for Markovian jump CPS (MJCPS). Firstly, considering that the feedback state information is compromised by adversaries, a compromised state variable-dependent switching function is designed. Secondly, based on the compromised state variables, an attack compensator with projection-based adaptation laws are constructed. In this way, the attack related parameters can be adjusted online and the FDI attacks can be compensated adaptively. Then, the stochastically bounded stable of the overall closed-loop MJCPS and the reachability analysis for the constructed sliding surface are derived. Finally, a practical example about an F-404 aircraft engine system is employed to illustrate the efficacy of the proposed technique.